Interferon-gamma-induced transcriptional activation is mediated by protein kinase C. - Xuerong Fan; Michael F. Goldberg; Barry R. Bloom (1988)
Interferon-gamma (IFN-gamma) regulates a variety of biological functions and is the principal lymphokine known to activate macrophages. In studies of the molecular mechanisms by which these cells are regulated by IFN-gamma, the transcriptional activation of an IFN-gamma-inducible gene, gamma.1, in human macrophage-like cell lines was examined. Transcription of this gene is rapidly induced by 0.1-1 unit of IFN-gamma. In addition, gamma.1 transcription is efficiently induced by phorbol 12-myristate 13-acetate, which is known to activate protein kinase C (PKC). Both stimulators of gamma.1 transcription induce the translocation of PKC from the cytosol of a membrane fraction. Two selective inhibitors of PKC, H7 and sphingosine, suppressed not only the induction of gamma.1 mRNA but transcription of HLA-DR by IFN-gamma as well. These findings establish that PKC plays a significant role in the signal transduction pathway leading to transcriptional activation of some IFN-gamma-regulated genes of cells of the mononuclear phagocyte lineage.